Gandhian School of Educational Thought - Charles B Berebon (dialektika kontemporer, 2023)
In the changing global scenario, the main aim of education is to help people develop themselves as global and local responsible citizens who will make conscientious efforts for building a humane world with peace and harmony. The focus of education should be the development of values of peace and harmony based on the human mindset: human rights, mutual respect, mutual trust, cooperation, respect for life, social justice, open-mindedness, and co-existence. Keeping this in mind, it is necessary to reorient and restructure the education programme to include education for peace and harmony. The essence of this work is to expose the Gandhian school of educational thought. This work argues that trusteeship is a unique socio-economic doctrine of Gandhi; however, it has not received the serious attention of social scientists. This study examines trusteeship from a holistic perspective, which is an approach favoured by Gandhi. It highlights the theoretical and practical aspects of trusteeship and examines its present-day relevance.